JUAL BELI BAI’UL WAFA’ DITINJAU MENURUT HUKUM ISLAM - Hasan Syazali (Jurnal Tahqiqa : Jurnal Ilmiah Pemikiran Hukum Islam, 2019)
This writing aims to examine the fundamental problems, namely thenotion of buying and selling bai'ul wafa ', and the view of Islamic law on buyingand selling (bai' wafa '). The results of the writing show that the practice of buyingand selling bai'ul wafa ', which is in the community is buying and selling bymeans of credit, and the provision is done by paying down and installments everymonth when the payment due date, where the company makes it easy for everyconsumer for consumers is a major factor to attract buyers to buy products offeredby the company, while from consumers one of them is the needs of customerswho are urgent but not enough money. Furthermore, the view of Islamic law onbuying and selling (bai 'wafa'). Islam allows wafa sale, because the buyer mustfulfill his promise between the seller, this is done in the initial agreement of thetransaction, while this transaction is included in the sale and purchase trust andmutual trust, because the merchandise that has been purchased becomes amandate for the buyer to return to the seller if the seller returns the money, and thebuyer may not sell the item to another person, other than returning it to the seller.